Improving the Metal Inert Gas Welding Efficiency and Microstructural Stability in the Butt and Lap Joints of Aluminum Automotive Components Using Sc- and Zr-Enhanced Filler Wires - Hansol Ko; Hye-Jin Kim; Dong-Yoon Kim; Jiyoung Yu (Metals)
The grain growth in the fusion zone (FZ) and heat-affected zone (HAZ) of metal inert gas (MIG) welding processes negatively affect the mechanical properties of aluminum alloy MIG welds used in automotive components. Although the addition of Sc- and Zr-based filler wires can refine weld microstructures and enhance the mechanical properties, conditions resembling actual automotive component joints have not been sufficiently investigated. In this study, 5083-O aluminum alloy base material was welded into butt and lap joints using conventional 5000-series aluminum alloy filler wires (Al-5.0Mg) and wires containing Sc and Zr (Al-4.8Mg-0.7Sc-0.3Zr) under various heat input conditions. The mechanical properties of the welds were evaluated via tensile tests, and the microstructures in the FZ and HAZ were analyzed. In butt joints, Al-4.8Mg-0.7Sc-0.3Zr exhibited a finer and more uniform grain structure with increased tensile strength compared with those welded using Al-5.0Mg. The microstructure became coarser with the increased heat input, and the tensile strength tended to decrease. In lap joints, the tensile-shear strength of Al-4.8Mg-0.7Sc-0.3Zr was higher than that of Al-5.0Mg; it further increased with the increase in the amount of deposited metal. The coarsening of the microstructure with the increased heat input was disadvantageous for the tensile-shear strength, and the increased weld size offset the adverse effects of the coarse microstructure. These results indicate that the heat input and the amount of deposited metal must be optimized to ensure stiffness in various joints of automotive components.